An Analysis of Student’s Critical Thinking Skills in Writing Argumentative Essay - Voresti Sabu; Bernard Vernandes (English Department, Faculty of Humanities, Andalas University, 2019)
Writing is a communication tool to deliver thoughts and ideas in written form. Generally, in writing an argumentative essay, students do not provide their supporting arguments and do not provide evidence to convince the readers and even believe at the writer. Students asked to comprehend how to develop their ideas or their thought based on elements of the argumentative essay as a guide for them in applying their thought or their critical thinking in writing English essay. Based on the problem above, the researchers analyzed students' critical thinking skills in writing an argumentative essay at STKIP Abdi Pendidikan Payakumbuh in 2017/2018 academic year. The population of this research was English department students on the second academic year at STKIP Abdi Pendidikan Payahkumbuh, and there were 13 sample students. In gathering the data, the instrument used by the researchers in this research was a written test. The researchers asked the students to write an argumentative essay about 300 words in 60 minutes. The instrument in this research has content validity based on SAP from SKTIP Abdi Pendidikan Payakumbuh 2017/2018 academic year, because the students had learned argumentative essay subject. The researchers used inter-rater reliability and coefficient reliability from two scorers to analyze students' critical thinking in writing an argumentative essay. The result revealed the student' critical thinking skills in writing an argumentative essay was 60, it belong to “average to good critical thinking skill category”.